MicroR-1199-5p targeting SRD5A2 promotes the biological behavior and EMT of hypospadias cells: MicroR-1199-5p promotes EMT in hypospadias cells - Chen, Yifu; Hu, Jianjun; Peng, Liucheng; Zhao, Yaowang (Cellular and Molecular Biology, 2024)
Hypospadias, an oft-occurring penis anomaly, ranks among neonatal's foremost birth defects. The SRD5A2 can affect male reproductive system development and is abnormally expressed in its epithelial cells. This study exploration aimed at understanding the role of SRD5A2 in the development of hypospadias from a molecular perspective. SRD5A2 levels in hypospadias primary cells were analyzed by Western blot, while targeted interaction with miR-1199-5p was ascertained by dual-luciferase gene reporter assay. In vitro biological experiments were used to confirm the biological function of SRD5A2 in hypospadias. SRD5A2 expression was significantly upregulated, and miR-1199-5p expression was significantly downregulated in hypospadias primary cells. Intervention of SRD5A2 expression can affect cell proliferation, migration, invasion, EMT, and the expression of cell cycle-related proteins. Additionally, we found that SRD5A2 is regulated by upstream miR-1199-5p and can enhance the effect of SRD5A2 on hypospadias cells. Conclusions Silencing SRD5A2 promotes cell proliferation, invasion, and migration blocks the cell cycle at the G1 phase, and simultaneously promotes EMT, cell cycle, and cell proliferation-related protein expression. The biological function of SRD5A2 in hypospadias cells is regulated by miR-1199-5p. SRD5A2 may be an effective therapeutic target for hypospadias.